Андеркласс и культура бедности в среде бывших государственных сельских хозяйств в контексте теоретических и интерпретационных дискуссий - Карвацкий, А.; Антонович, Д. (Социология: теория, методы, маркетинг, 2005)
For years state farm (and later exstate farm) communities have been shaping a specific syndrome of the so called “culture of poverty”. The community members do not receive any social capital by virtue of upbringing or education. Social scientists noticed potential for underclass formation among exstate farm workers. Despite the fact that the above mentioned process has been going on for years, researchers still express doubts as to the possibility of underclass formation in Poland, which may be due to interpretative and terminological discrepancies as well as the specific modeling of this phenomenon. Our paper deals with the subject of possible emergence of underclass in Poland in the context of English theoretical debates, backed by classical American reflections. We shall try to show that in discussions on the nature of underclass, we can actually abandon the disagreements stemming from the primacy of structural or cultural factors in the complex process of underclass formation. Our research and literature review suggest that we can identify an existing Polish underclass (of a local character), which created its own system of behavior, values and norms, which can be described as a “culture of poverty”.